Pengaruh Media Sosial terhadap Keberhasilan Usaha Pengusaha Cafe di Jember dengan Motivasi sebagai Variabel Intervening - Aldith Maulana, Ezar; Nurul Qomariah; Jekti Rahayu (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
Cafes in Jember Regency continue to grow significantly amid increasingly fierce competition among businesses and the rise of MSMEs in the digital era. The culinary industry, particularly the café sector in Jember Regency, has seen significant growth, presenting promising opportunities for café owners and a substantial market. Numerous cafés are spread across various neighborhoods in Jember Regency. This study focuses on how social media can be utilized for customer engagement and promotion. Additionally, entrepreneurial motivation is examined as a factor that can enhance the influence of these elements on business success. To explore the relationships among these factors, data was gathered through questionnaires and analyzed using multiple linear regression techniques. A quantitative survey approach was used to collect information from 100 cafe owners in Jember. The findings showed that social media significantly and positively influenced motivation and company success. In addition, motivation was found to be an intervening variable that strengthens the impact of these elements on cafe business success.